Bravelands : Realm of Lost Spirits - Book 3 - Hunter, Erin (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2024)
"Bravelands faces its final test. As water dwindles and food becomes scarce, Whisper the water buffalo must embrace a strength she never knew. Stride the cheetah embarks on a dangerous journey--a final attempt to bring rain to Bravelands. But the quest will lead him into the underworld of spirits, where his most fearsome enemy awaits. And Breathstealer the hyena faces a choice. The Great Devourer pours poison in her ear, promising strength and survival for her and her entire clan. But his plans would send her down a dark path of no return. Can Bravelands come together to vanquish this great evil? Or will their home be torn apart?"--
Keywords: Cheetah -- Juvenile fiction; Water buffalo -- Juvenile fiction; Hyenas -- Juvenile fiction; Good and evil -- Juvenile fiction; Animals -- Juvenile fiction. -- Africa; Cheetahs -- Fiction; Water buffaloes -- Fiction; Hyenas -- Fiction; Good and evil -- Fiction; Animals -- Fiction. -- Africa; Africa -- Juvenile fiction; Africa -- Fiction; Animal fiction; Fantasy fiction; Action and adventure fiction